Cytomegalovirus-Mediated T Cell Receptor Repertoire Perturbation Is Present in Early Life - Attaf, Meriem; Roider, Julia; Malik, Amna; Rius Rafael, Cristina; Dolton, Garry; Prendergast, Andrew J.; Leslie, Alasdair; Ndung'u, Thumbi; Kløverpris, Henrik N.; Sewell, Andrew K.; Goulder, Philip J. (Frontiers in Immunology, 2020)
Human cytomegalovirus (CMV) is a highly prevalent herpesvirus, particularly in sub-Saharan Africa, where it is endemic from infancy. The T cell response against CMV is important in keeping the virus in check, with CD8 T cells playing a major role in the control of CMV viraemia. Human leukocyte antigen (HLA) B*44:03-positive individuals raise a robust response against the NEGVKAAW (NW8) epitope, derived from the immediate-early-2 (IE-2) protein. We previously showed that the T cell receptor (TCR) repertoire raised against the NW8-HLA-B*44:03 complex was oligoclonal and characterised by superdominant clones, which were shared amongst unrelated individuals, i.e. ‘public’. Here, we address the question of how stable the CMV-specific TCR repertoire is over the course of infection, and whether substantial differences are evident in TCR repertoires in children, compared with adults. We present a longitudinal study of four HIV/CMV co-infected mother-child pairs, who in each case express HLA-B*44:03 and make responses to the NW8 epitope, and analyse their TCR repertoire over a period spanning more than 10 years. Using high-throughput sequencing, the paediatric CMV-specific repertoire was found to be highly diverse. In addition, paediatric repertoires are remarkably similar to adults, with public TCR responses being shared amongst children and adults alike. The CMV-specific repertoire in both adults and children displayed strong fluctuations in TCR clonality and repertoire architecture over time. Previously characterised superdominant clonotypes were readily identifiable in the children at high frequency, suggesting that the distortion of the CMV-specific repertoire is incurred as a direct result of CMV infection rather than a product of age-related ‘memory inflation’. Early distortion of the TCR repertoire was particularly apparent in the case of the TCR-β chain, where oligoclonality was low in children and positively correlated with age, a feature we did not observe for TCR-α. This discrepancy between TCR-α and -β chain repertoire may reflect differential contribution in NW8 recognition. Altogether, the results of the present study provide insight into the formation of the TCR repertoire in early life and pave the way to better understanding of CD8 T cell responses to CMV at the molecular level.